2019
DOI: 10.1038/s41422-019-0189-9
|View full text |Cite
|
Sign up to set email alerts
|

NDP52 tunes cortical actin interaction with astral microtubules for accurate spindle orientation

Abstract: Oriented cell divisions are controlled by a conserved molecular cascade involving Gαi, LGN, and NuMA. Here, we show that NDP52 regulates spindle orientation via remodeling the polar cortical actin cytoskeleton. siRNA-mediated NDP52 suppression surprisingly revealed a ring-like compact subcortical F-actin architecture surrounding the spindle in prophase/prometaphase cells, which resulted in severe defects of astral microtubule growth and an aberrant spindle orientation. Remarkably, NDP52 recruited the actin ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 56 publications
3
20
0
Order By: Relevance
“…Thus, our findings indicate that defects in astral microtubules and spindle orientation upon ANXA1 depletion are likely to cause incorrect chromosome segregation. This is consistent with evidence suggesting that unbalanced astral microtubule-cortex cross talk leads to defective chromosome dynamics 4,61 . It will be interesting to explore further the molecular mechanisms linking ANXA1-mediated regulation of astral microtubule dynamics to accurate chromosome segregation.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, our findings indicate that defects in astral microtubules and spindle orientation upon ANXA1 depletion are likely to cause incorrect chromosome segregation. This is consistent with evidence suggesting that unbalanced astral microtubule-cortex cross talk leads to defective chromosome dynamics 4,61 . It will be interesting to explore further the molecular mechanisms linking ANXA1-mediated regulation of astral microtubule dynamics to accurate chromosome segregation.…”
Section: Discussionsupporting
confidence: 92%
“…The CC membrane binding site is also important for binding, but residual binding still occurs in when the CC membrane binding site is removed. We tested whether NDP52 itself could bind membranes as previously reported (H. Yu et al, 2019). NDP52 was recruited to the GUV membranes either when it was tagged with GST or upon the addition of poly-ubiquitin ( Figure S5).…”
Section: Ndp52 Binding Is Required For the Membrane Recruitment Of Ulk1mentioning
confidence: 98%
“…Computational modeling of the spindle positioning process suggests a mechanism by which the ring-like F-actin structure regulates astral microtubule dynamics and mitotic spindle orientation. Yu and colleagues found that NDP52, a membrane organelle regulator, regulates spindle orientation by remodeling the polar F-actin structure (81). Mechanistically, NDP52 binds to phosphatidic acid-containing vesicles to enable NDP52-containing vesicles to anchor to the actin assembly factor N-WASP via a physical interaction and thereby shorten actin filaments.…”
Section: Spindle Plasticity and Membraneless Organelle Dynamics In Cementioning
confidence: 99%